Soccer - Steward, P.; Springham, M. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
Soccer is the world`s most popular sport, with the Federation of the International Football Association (FIFA) estimating that more than 270 million people are actively involved in the sport worldwide. Like many sports, successful performance requires a multitude of interconnecting factors, such as technical, tactical, psychological and physical proficiency. Although the application of sport science in soccer is relatively new, it is accepted that the application of sport science can assist in enhancing performance and reducing the risk of injury. With the ever-increasing financial incentives (professional contracts, sponsorships, TV rights) within the professional world, it is perhaps unsurprising that the demand for scientific support services such as strength & conditioning (S&C) has increased. In elite performance environments it is essential to understand the athletic demands of the sport. Such information enables the S&C coach to optimise the training and recovery process to ensure the player is physically prepared for the rigors of competition. Advancements in sport science technology has enabled scientists and practitioners to quantify the physical demands of soccer through such means as ime motion analysis (semi-automated video analysis systems & global positioning system (GPS)), heart rate (HR) monitoring, biological markers (typically blood and salivary analysis) and perceived exertion (sRPE). Such information allows the S&C coach to select relevant fitness tests and appropriately plan and periodise programmes to optimise performance and reduce the risk of injury. The aim of this chapter is to review the athletic demands and injury prevalence, identify appropriate fitness tests, and provide practical guidance in programming.